Do children mature like apples? (Journal of Parents and Teachers, 2026)
It is explained that the mission of the educational authority is not to impose personal maturity on children, but to help them achieve it. Fernando de la Puente criticises consumerism and society, as these factors cause us to forget the happiness and authenticity of children. We must educate for maturity, to develop confident and free individuals.
Keywords: Maturity, Self-Esteem, Autonomy, Values, and Education.